Nano antibacterial air filtering hot air nonwoven fabric and preparation method thereof
By using the structure of nano -AG/TIO2 composite air gel antibacterial layer and multi -layer air filter layer in non -woven fabrics, the problem of uneven distribution of nano -silver on the surface of non -woven fabrics is solved, and uniform antibacterials and antibacterials of non -woven fabrics are realized. Efficient air filtration effect.
Patent Information
- Application Number
- CN202211582499.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The uneven distribution of nano silver on the surface of non-woven fabrics leads to uneven antibacterial effects and there is no antibacterial effect locally.
The structure of the upper and lower layers of air filter layer and the intermediate antibacterial layer is generated by the hot air process. The antibacterial layer includes the nano -AG/TiO2 composite gas gel antibacterial non -woven, resin layer and non -woven fabric, which are fixed through the acupuncture process.
Improve the air filtration capacity and antibacterial ability of non -woven fabrics, ensure the uniform distribution and strength of the antibacterial layer, and avoid the phenomenon of local antibacterial effects.
Smart Images

Figure BDA0003991898560000051 
Figure BDA0003991898560000052 
Figure BDA0003991898560000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of non-woven fabrics, and in particular to a nano antibacterial air filtering hot air non-woven fabric and a preparation method thereof. Background Art
[0002] Hot air nonwoven fabric is a type of hot air bonded nonwoven fabric. After the fibers are combed, the hot air on the drying equipment is used to penetrate the fiber web, causing it to be heated and bonded. Nanosilver can combine with DNA in bacteria, displace the hydrogen bonds in the double helix structure of DNA molecules, change the structure of DNA, inhibit the replication of bacterial DNA, and thus destroy the bacterial reproduction function to kill bacteria. Grafting nanosilver on the surface of nonwoven fabric can make the nonwoven fabric have antibacterial properties.
[0003] For related technologies, reference may be made to the Chinese invention patent with authorization announcement number CN102644162B, which discloses a method for preparing a non-woven fabric based on a nano-silver single-substance antibacterial agent, wherein the nano-silver sol is dried and crushed to obtain a nano-silver single-substance powder; then, a non-woven fabric spinning resin, a nano-silver single-substance powder, a coupling dispersant, and a discoloration inhibitor are mixed and granulated to obtain an antibacterial masterbatch; and then conventional spinning is performed to obtain the antibacterial non-woven fabric.
[0004] With respect to the above-mentioned related technologies, the inventors believe that the defects are as follows: since the particle size of the nanosilver particles is very small, the surface lacks adjacent coordinated atoms and has high activity, the nanosilver particles are prone to agglomeration with each other, resulting in uneven distribution of the nanosilver on the surface of the non-woven fabric, which leads to uneven antibacterial effect on the surface of the non-woven fabric and the phenomenon of no antibacterial effect in some parts. Summary of the invention
[0005] In order to improve the antibacterial ability of non-woven fabrics, the present application provides a nano antibacterial air filtering hot air non-woven fabric and a preparation method thereof.
[0006] The nano antibacterial air filtration hot air nonwoven fabric provided in this application adopts the following technical solution:
[0007] A nano antibacterial air filtration hot air nonwoven fabric comprises an upper and lower air filtration layer and an intermediate antibacterial layer, which is bonded by a hot air process. The antibacterial layer comprises nano Ag / TiO 2 Composite aerogel antibacterial non-woven fabric, resin layer, non-woven fabric, the resin layer is coated between two layers of non-woven fabric, and fixedly connected by a needle punching process; the nano Ag / TiO 2 The composite aerogel comprises the following raw materials by weight: 20-35 parts of ethyl titanate, 0.5-0.8 parts of silver nitrate, 3.1-4.5 parts of hydrazine hydrate, 8-15 parts of N,N-dimethylformamide, 15-20 parts of deionized water, and 40-58 parts of ethanol.
[0008] By adopting the above technical scheme, a nano antibacterial air filtering hot air non-woven fabric is formed by bonding the upper and lower air filtering layers and the middle antibacterial layer, so that the air filtering ability and antibacterial ability of the non-woven fabric can be improved.
[0009] Preferably, the air filter layer is formed by bonding several layers of polyethylene non-woven fabrics.
[0010] By adopting the above technical scheme, multiple layers of non-woven fabrics are bonded to form the filter layer. This is because the fiber structure of the non-woven fabric is loose and the porosity is high, which can effectively filter and remove solid and soft particles. Polyethylene non-woven fabric is a new generation of environmentally friendly material. It is also water-repellent, breathable, flexible, non-combustible, non-toxic and non-irritating. It can improve the air filtration and breathability of nano antibacterial air filtration hot air non-woven fabric.
[0011] Preferably, the resin layer is 13-18 parts of acrylic resin.
[0012] By adopting the above technical solution and using a resin layer, the antibacterial layer can be effectively bonded and cured, and acrylic resin has good stability to light, heat and chemicals. The strength of the nano antibacterial air filtration hot air non-woven fabric can be improved through the bonding of the resin layer.
[0013] The present application provides a method for preparing a nano antibacterial air filtering hot air nonwoven fabric using the following technical solution:
[0014] A method for preparing a nano antibacterial air filtering hot air nonwoven fabric comprises the following steps:
[0015] S1. Several portions of polyester fiber nonwoven fabric were immersed in 75% ethanol solution, and then washed and dried to obtain a pretreated nonwoven fabric;
[0016] S2. A portion of pre-treated non-woven fabric was impregnated with nano-Ag / TiO 2 The composite aerogel was placed in the antibacterial liquid for 20-30 minutes to obtain nano-Ag / TiO 2 Composite aerogel wet nonwoven fabric; Nano-Ag / TiO 2 The composite aerogel wet nonwoven fabric was dried at 90-110°C for 5-8h to obtain nano-Ag / TiO 2 Composite aerogel antibacterial nonwoven fabric;
[0017] S3. 13-18 parts of acrylic resin are coated on the nano Ag / TiO 2 On the composite aerogel nonwoven fabric, another pretreated nonwoven fabric is laid on top of the acrylic resin, and the laid nonwoven fabric is fixed by needle punching to obtain an antibacterial layer;
[0018] S4. Stack several layers of polyethylene non-woven fabrics in sequence to obtain an air filter layer; lay an antibacterial layer between two adjacent air filter layers, and hot-air bond the laid non-woven fabrics at 165-170° C. to obtain a nano antibacterial air filter hot-air non-woven fabric.
[0019] By adopting the above technical scheme, polyester fiber non-woven fabric is used. Polyester fiber non-woven fabric is a water-repellent non-woven fabric with good water-repellent performance. If there are water droplets on the surface of the polyester fiber non-woven fabric, the water droplets will slide directly from the surface; and the polyester fiber non-woven fabric has excellent strength, good air permeability, chemical resistance and anti-aging performance; the polyester fiber non-woven fabric is pre-treated with an ethanol solution to remove dust, floating hair and other substances on the top of the non-woven fabric, which is conducive to better bonding of the antibacterial liquid.
[0020] Preferably, the process conditions for the acupuncture fixation are as follows: acupuncture frequency of 1200 punctures / min, acupuncture density of 6000 pieces / m, acupuncture speed of 1 m / min, and acupuncture depth of 5-8 mm.
[0021] By adopting the above technical scheme, the antibacterial layer is fixed by needle puncture, which not only improves the strength of the antibacterial layer, but also does not destroy the antibacterial properties of the antibacterial layer during the fixing process. At the same time, fixation by needle puncture can also improve the air permeability and filtration performance of the antibacterial layer, thereby improving the air permeability and filtration performance of the nano antibacterial air filtration hot air non-woven fabric.
[0022] Preferably, the nano Ag / TiO 2 The composite aerogel antibacterial liquid includes 3-6 parts by weight of nano-Ag / TiO 2 Composite aerogel, 60-80 parts of anhydrous ethanol, 7-11 parts of polyethylene glycol, 1.8-3 parts of defoaming agent, and 1-3 parts of nano titanium dioxide.
[0023] By adopting the above technical scheme, polyethylene glycol can be used as a dispersant to adsorb and wrap the nanoparticles, thereby giving the particles charge and steric hindrance and controlling the aggregation of the particles. At the same time, polyethylene glycol can also play a curing role to improve the sufficiency of the bonding between the antibacterial liquid and the pretreated non-woven fabric; the defoaming agent can eliminate the bubbles generated in the antibacterial liquid to avoid uneven bonding of the antibacterial liquid; the nano-titanium dioxide can not only play the role of a sunscreen, but also has antibacterial, self-cleaning and anti-aging properties, thereby improving the antibacterial properties of the nano-antibacterial air filtration hot air non-woven fabric.
[0024] Preferably, the nano Ag / TiO 2 The preparation method of the composite aerogel comprises the following steps:
[0025] S1. Add 15-20 parts of deionized water and 30-45g of ethanol to 20-35 parts of ethyl titanate, mix well, add acetic acid to adjust the pH to 6-7 to obtain solution A;
[0026] S2. Add 0.5-0.8 parts of silver nitrate to 10-13 parts of ethanol, add the mixed solution to solution A and mix well, stir at 50-65°C for 2-4 hours; add 3.1-4.5 parts of hydrazine hydrate and continue the reaction; add 8-15 parts of N,N-dimethylformamide to the mixed solution and stir well to obtain Ag / TiO 2 Sol;
[0027] S3. Ag / TiO 2 The sol was dried at 40-50°C for 12-36h to obtain Ag / TiO 2 Gel; Ag / TiO 2 The gel was immersed in anhydrous ethanol for 20-30h, and then the Ag / TiO 2 The gel was immersed in a mixed solution of anhydrous ethanol and n-hexane (1:1-2) for 20-30 hours. 2 The gel was dried to obtain nano-Ag / TiO 2 Composite aerogel.
[0028] By adopting the above technical solution, nano Ag / TiO 2 Composite aerogel can improve the antibacterial performance and air permeability of nano antibacterial air filtration hot air non-woven fabric. Nanosilver can combine with DNA in bacteria, replace the hydrogen bonds of the double helix structure of DNA molecules, change the structure of DNA, inhibit the replication of bacterial DNA, and thus destroy the bacterial reproduction function to kill bacteria; by carrying with titanium dioxide aerogel, the phenomenon of easy agglomeration of single nanosilver particles can be improved, and the antibacterial performance can be improved; at the same time, titanium dioxide aerogel is light in weight, has high porosity, high temperature resistance, strong pressure resistance, and good air permeability. The composite of nanosilver titanium dioxide aerogel not only improves the antibacterial ability of non-woven fabrics, but also improves the air permeability and air filtration ability of non-woven fabrics. The ethanol solution is used because ethyl titanate is easily hydrolyzed in water. Ethanol can be used to dilute ethyl titanate, form a steric barrier, and alleviate the hydrolysis of ethyl titanate. Hydrazine hydrate is used because hydrazine hydrate has a strong reducing property and can prepare a stable nano Ag / TiO 2 Composite aerogel. Using N,N-dimethylformamide can improve the pore structure of aerogel and enhance the stability of aerogel.
[0029] Preferably, the reaction conditions of the drying reaction are as follows: the reaction temperature is 60-80° C., and the reaction time is 24-48 h.
[0030] By adopting the above technical scheme, nano Ag / TiO 2 Composite aerogel can improve the nano-Ag / TiO 2 The specific surface area of the composite aerogel increases the surface activity of the metal, which is beneficial to the activity of the surface technology and improves the nano-Ag / TiO 2 Antibacterial ability and air filtration of composite aerogels.
[0031] In summary, the present application includes at least one of the following beneficial technical effects:
[0032] 1. By adopting the above technical solution, a nano antibacterial air filtering hot air non-woven fabric is formed by bonding the upper and lower air filtering layers and the middle antibacterial layer, which can improve the air filtering ability and antibacterial ability of the non-woven fabric;
[0033] 2. By adopting the above technical solution, nano Ag / TiO 2 Composite aerogel can improve the antibacterial performance and air permeability of nano antibacterial air filtration hot air nonwoven fabric;
[0034] 3. By adopting the above technical scheme, the antibacterial layer is fixed by needle puncture, which not only improves the strength of the antibacterial layer, but also does not destroy the antibacterial properties of the antibacterial layer during the fixing process. At the same time, fixation by needle puncture can also improve the air permeability and filtration performance of the antibacterial layer, thereby improving the air permeability and filtration performance of the nano antibacterial air filtration hot air non-woven fabric. DETAILED DESCRIPTION
[0035] The present application is further described in detail below in conjunction with the embodiments.
[0036] Example
[0037] Example 1
[0038] S1. 15 g of deionized water and 30 g of ethanol were slowly added to 20 g of ethyl titanate, stirred at 40 ° C for 30 min, and acetic acid was added to adjust the pH to 7 to obtain solution A;
[0039] S2. Add 0.5g of silver nitrate solution to 10g of ethanol, add the mixed solution to solution A and mix well, stir in a water bath at 50°C for 2h; add 3.1g of hydrazine hydrate and continue to react for 30min; add 8g of N,N-dimethylformamide, stir well, and let stand for 2h to obtain Ag / TiO 2 Sol.
[0040] S3. Ag / TiO 2 The sol was placed in a drying oven and dried at 40 °C for 12 h to obtain Ag / TiO 2 Gel; Ag / TiO 2The gel was immersed in anhydrous ethanol at 40 °C for 20 h. 2 The gel was immersed in a mixed solution of anhydrous ethanol and n-hexane in a ratio of 1:2 for 20 h. 2 The gel was dried at 60 °C for 24 h to obtain nano-Ag / TiO 2 Composite aerogel.
[0041] S4. Prepared nano-Ag / TiO 2 The composite aerogel was ground to 500 mesh and 3 g of nano-Ag / TiO 2 The composite aerogel was added to 60 kg of anhydrous ethanol, 7 kg of polyethylene glycol, 1 kg of nano titanium dioxide, and 1.8 kg of a polyether defoamer. The defoamer used in this embodiment was GP-330. The mixture was stirred at 1200 rpm for 1 h to obtain a nano Ag / TiO 2 Composite aerogel antibacterial liquid.
[0042] S5. Put two 400cm 2 The polyester fiber non-woven fabric was immersed in a 75% ethanol solution for 4 hours, taken out, washed with deionized water, and dried in a drying oven at 110° C. to obtain a pretreated non-woven fabric.
[0043] S6. Nano-Ag / TiO 2 The composite aerogel antibacterial liquid was placed in an immersion tank, and one of the pretreated nonwoven fabrics was immersed in the mixed antibacterial liquid for 30 min to obtain nano-Ag / TiO 2 Composite aerogel wet nonwoven fabric, nano-Ag / TiO 2 The composite aerogel wet nonwoven fabric was placed in a drying oven and dried at 110 °C for 5 h. After drying, nano-Ag / TiO 2 Composite aerogel antibacterial nonwoven fabric.
[0044] S7. 13 kg of acrylic resin is evenly coated on the nano-Ag / TiO 2 On one side of the composite aerogel non-woven fabric, another pretreated non-woven fabric is laid on top of the acrylic resin, and the laid non-woven fabric is sent into a needle-punched non-woven fabric machine, and is fixed by needle punching at a needle punching frequency of 1200 times / min, a needle punching density of 6000 pieces / m, a speed of 1 m / min, and a needle punching depth of 5 mm to obtain an antibacterial layer.
[0045] S8. Put two 400cm 2 The polyethylene non-woven fabrics are stacked in sequence to obtain an air filter layer, the antibacterial layer made by S7 is laid between the upper and lower air filter layers, the laid non-woven fabrics are sent into a hot air blower, and hot air bonding is performed at 240-280°C to obtain a nano antibacterial air filter hot air non-woven fabric.
[0046] Example 2-11
[0047] The difference between Example 2-11 and Example 1 is that in Example 2-11, nano Ag / TiO 2 The process parameters of composite aerogel are different, as shown in Table 1.
[0048] Table 1 Preparation of Nano-Ag / TiO in Examples 2-11 2 Process parameters of composite aerogel
[0049]
[0050] Table 2 Preparation of Nano-Ag / TiO in Examples 12-13 2 Process parameters of composite aerogel
[0051]
[0052] Examples 14-17
[0053] The difference between Examples 12-17 and Example 1 is that the process parameters for preparing the antibacterial layer in Examples 12-17 are different, as shown in Table 3.
[0054] Table 3 Process parameters for preparing antibacterial layer in Examples 12-17
[0055]
[0056] Examples 22-23
[0057] The difference between Example 22-23 and Example 1 is that the process parameters for needle fixation of the preparation of the antibacterial layer in Examples 22-23 are different, as shown in Table 4.
[0058] Table 4 Process parameters for acupuncture fixation of the antibacterial layer prepared in Examples 22-23
[0059]
[0060] Comparative Example
[0061] Comparative Examples 1-10
[0062] The difference between Comparative Examples 1-10 and Example 1 is that the nano Ag / TiO 2 The process parameters of composite aerogel are different, as shown in Table 5.
[0063] Table 5 Preparation of Nano-Ag / TiO in Comparative Examples 1-10 2 Process parameters of composite aerogel
[0064]
[0065]
[0066] Comparative Examples 11-16
[0067] The difference between Comparative Examples 11-16 and Example 1 is that the process parameters for preparing the antibacterial layer in Comparative Examples 11-16 are different, as shown in Table 6.
[0068] Table 6 Process parameters for preparing antibacterial layer in Comparative Examples 11-16
[0069]
[0070] Comparative Example 17
[0071] The difference between Comparative Example 17 and Example 1 is that the air filter layer in Comparative Example 17 is composed of a polyethylene non-woven fabric.
[0072] Performance testing
[0073] 1. According to GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the antibacterial properties of the nano antibacterial air filtering hot air non-woven fabrics prepared in Examples 1-23 and Comparative Examples 1-18 were tested.
[0074] 2. According to GB / T24218.3-2010 "Test methods for textiles and nonwovens Part 3: Determination of breaking strength and breaking elongation", the breaking strength of the nano antibacterial air filtering hot air nonwoven fabrics prepared in Examples 1-23 and Comparative Examples 1-18 was tested.
[0075] 3. According to GB / T24218.15-2018 "Test methods for textiles and nonwoven fabrics Part 15: Determination of air permeability", the air permeability of the nano antibacterial air filtration hot air non-woven fabrics prepared in Examples 1-23 and Comparative Examples 1-18 was tested.
[0076] 4. According to / 14295-2008 "Air Filter", the air filtration efficiency of the nano antibacterial air filtration hot air non-woven fabrics prepared in Examples 1-23 and Comparative Examples 1-18 was tested.
[0077]
[0078]
[0079] It can be seen from the test results of Examples 1-3 and Comparative Examples 1-2 that when preparing nano-Ag / TiO2 composite aerogel, the more the mass of silver nitrate, the stronger the antibacterial property of the obtained nano-antibacterial air filtration hot air non-woven fabric. When the mass of silver nitrate exceeds 0.8g, the antibacterial property of the non-woven fabric no longer changes; the change in the mass of silver nitrate has little effect on the breaking strength, air permeability and air filtration efficiency of the nano-antibacterial air filtration hot air non-woven fabric.
[0080] From the test results of Examples 1, 4, 5 and Comparative Examples 3, 4, it can be seen that the preparation of nano-Ag / TiO 2 When composite aerogel, the more the mass of ethyl titanate, the higher the antibacterial property of the obtained nano antibacterial air filtration hot air non-woven fabric, but when the mass of ethyl titanate reaches 35g, the antibacterial property of the non-woven fabric no longer changes; the change in the mass of ethyl titanate has little effect on the breaking strength, air permeability and air filtration efficiency of the nano antibacterial air filtration hot air non-woven fabric.
[0081] From the test results of Examples 1, 6, 7 and Comparative Examples 5 and 6, it can be seen that the preparation of nano-Ag / TiO 2 When composite aerogel, when the mass of hydrazine hydrate increases, the antibacterial property of the obtained nano antibacterial air filtration hot air non-woven fabric becomes stronger, but when the mass of hydrazine hydrate reaches 35g, the antibacterial property of the non-woven fabric no longer changes; the change in the mass of hydrazine hydrate has little effect on the breaking strength, air permeability and air filtration efficiency of the nano antibacterial air filtration hot air non-woven fabric.
[0082] From the test results of Examples 1, 8, 9 and Comparative Examples 7, 8, it can be seen that the preparation of nano-Ag / TiO 2 When the composite aerogel is prepared, the temperature of the drying reaction increases, and the antibacterial property of the obtained nano antibacterial air filtration hot air non-woven fabric shows a trend of first increasing and then decreasing. When the temperature reaches 70°C, the antibacterial property begins to decrease. At the same time, the increase in the drying reaction temperature also has an impact on the air permeability and air filtration efficiency of the non-woven fabric, and both show a trend of first increasing and then decreasing. When the temperature reaches 70°C, the air permeability and air filtration efficiency of the non-woven fabric begin to decrease. The change of the drying reaction temperature has little effect on the breaking strength of the nano antibacterial air filtration hot air non-woven fabric.
[0083] From the test results of Examples 1, 10, 11 and Comparative Examples 9 and 10, it can be seen that the preparation of nano-Ag / TiO 2 When composite aerogel is prepared, the drying reaction time increases, and the antibacterial properties, air permeability and air filtration efficiency of the obtained nano antibacterial air filtration hot air non-woven fabric also show a trend of first increasing and then decreasing. When the reaction time reaches 36h, the antibacterial properties, air permeability and air filtration efficiency begin to decrease; the change of drying reaction time has little effect on the breaking strength of the nano antibacterial air filtration hot air non-woven fabric.
[0084] From the test results of Examples 1, 12, and 13, it can be seen that the preparation of nano-Ag / TiO 2 The weight proportions of N,N-dimethylformamide, deionized water and ethanol in the composite aerogel have little effect on the antibacterial property, breaking strength, air permeability and air filtration efficiency of the obtained nano antibacterial air filtering hot air nonwoven fabric.
[0085] From the test results of Examples 1, 14, 15 and Comparative Examples 11, 12, it can be seen that in the preparation of nano-Ag / TiO 2 When composite aerogel antibacterial layer, nano Ag / TiO 2 The greater the mass of the composite aerogel, the stronger the antibacterial property of the nano antibacterial air filtration hot air nonwoven fabric. At the same time, the breaking strength, air permeability and air filtration efficiency of the nonwoven fabric also gradually increase. 2 When the mass of composite aerogel is increased, the antibacterial property, breaking strength, air permeability and air filtration efficiency of nano antibacterial air filtration hot air non-woven fabric no longer change.
[0086] From the test results of Examples 1, 16, 17 and Comparative Examples 13, 14, it can be seen that in the preparation of nano-Ag / TiO 2 When the composite aerogel antibacterial layer is formed, when the mass of nano-titanium dioxide increases, the antibacterial property of the nano-antibacterial air filter hot air non-woven fabric becomes stronger. When the mass of nano-titanium dioxide reaches 3g, the antibacterial property of the nano-antibacterial air filter hot air non-woven fabric no longer changes. When the mass of nano-titanium dioxide increases, the air permeability and filtration efficiency of the nano-antibacterial air filter hot air non-woven fabric also gradually increase. When the mass of nano-titanium dioxide reaches 3g, it no longer increases. The change in the mass of nano-titanium dioxide has little effect on the breaking strength of the nano-antibacterial air filter hot air non-woven fabric.
[0087] From the test results of Examples 1, 18, 19 and Comparative Examples 15, 16, it can be seen that in the preparation of nano-Ag / TiO 2 When the composite aerogel antibacterial layer is formed, as the mass of the acrylic resin increases, the breaking strength of the obtained nano antibacterial air filtration hot air non-woven fabric increases accordingly. When the mass of the acrylic resin reaches 18 kg, the breaking strength no longer changes. The change in the mass of the acrylic resin has little effect on the antibacterial properties, air permeability and air filtration efficiency of the nano antibacterial air filtration hot air non-woven fabric.
[0088] It can be seen from the test results of Example 1 and Comparative Example 17 that by stacking two polyethylene non-woven fabrics as the air filter layer, the nano-antibacterial air filter hot air non-woven fabric has a stronger air filtration rate, greater breaking strength and antibacterial properties, and less effect on the air permeability of the non-woven fabric than by using one polyethylene non-woven fabric as the air filter layer.
[0089] It can be seen from the test results of Examples 1, 20 and 21 that the weight parts of anhydrous ethanol, polyethylene glycol and defoaming agent provided in the present application for preparing the antibacterial layer have little effect on the antibacterial properties, breaking strength, air permeability and air filtration efficiency of the obtained nano antibacterial air filtration hot air non-woven fabric.
[0090] It can be seen from the test results of Examples 1, 22, and 23 that the needle-punch fixation process parameters for preparing the antibacterial layer provided in the present application have little effect on the antibacterial properties, breaking strength, air permeability, and air filtration efficiency of the obtained nano antibacterial air filtration hot air non-woven fabric.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a nano antibacterial air filtration hot air nonwoven fabric, characterized in that: The following steps are involved: S1. The polyester nonwoven fabric was immersed in a 75% ethanol solution, and then washed and dried to obtain a pretreated polyester nonwoven fabric; S2. Immersing a portion of the pretreated polyester fiber nonwoven fabric in a nano-Ag / TiO2 composite aerogel antibacterial solution for 20-30 min to obtain a nano-Ag / TiO2 composite aerogel wet nonwoven fabric; drying the nano-Ag / TiO2 composite aerogel wet nonwoven fabric at 90-110 ° C for 5-8 h to obtain a nano-Ag / TiO2 composite aerogel antibacterial nonwoven fabric; S3. 13-18 parts of acrylic resin are coated on the nano-Ag / TiO2 composite aerogel nonwoven fabric, and another pretreated polyester fiber nonwoven fabric is laid on top of the acrylic resin, and the laid nonwoven fabric is fixed by acupuncture to obtain an antibacterial layer; S4. Several layers of polyethylene nonwoven fabric are stacked in sequence to obtain an air filter layer; an antibacterial layer is laid between two adjacent air filter layers, and the laid nonwoven fabric is hot-air bonded at 165-170°C to obtain a nano antibacterial air filter hot air nonwoven fabric; The process conditions of the acupuncture fixation are as follows: acupuncture frequency of 1200 punctures / min, acupuncture density of 6000 pieces / m, acupuncture speed of 1 m / min, and acupuncture depth of 5-8 mm; The nano-Ag / TiO2 composite aerogel antibacterial liquid comprises, by weight, 3-6 parts of nano-Ag / TiO2 composite aerogel, 60-80 parts of anhydrous ethanol, 7-11 parts of polyethylene glycol, 1.8-3 parts of defoaming agent, and 1-3 parts of nano-titanium dioxide; The preparation method of the nano Ag / TiO2 composite aerogel comprises the following steps: S1. Add 15-20 parts of deionized water and 30-45 parts of ethanol to 20-35 parts of ethyl titanate, mix well, add acetic acid to adjust the pH to 6-7, and obtain solution A; S2. Add 0.5-0.8 parts of silver nitrate to 10-13 parts of ethanol to obtain a mixed solution, add the mixed solution to solution A and mix well, and stir at 50-65° C. for 2-4 hours; add 3.1-4.5 parts of hydrazine hydrate and continue the reaction; add 8-15 parts of N,N-dimethylformamide to the mixed solution and stir well to obtain Ag / TiO2 sol; S3. Dry the Ag / TiO2 sol at 40-50°C for 12-36h to obtain Ag / TiO2 gel; immerse the Ag / TiO2 gel in anhydrous ethanol for 20-30h, and then immerse the Ag / TiO2 gel in a mixed solution of anhydrous ethanol and n-hexane in a ratio of 1: (1-2) for another 20-30h. After immersion, dry the Ag / TiO2 gel to obtain nano Ag / TiO2 composite aerogel; the reaction conditions of the drying reaction are as follows: the reaction temperature is 60-80°C, and the reaction time is 24-48h.
Citation Information
Patent Citations
Method for preparing antibacterial non-woven fabrics based on nano-silver monoatomic antibacterial agent
CN102644162B
Air filtering non-woven fabric for air inlet filter screen of air conditioner, and preparation method of air filtering non-woven fabric
CN106861287A
Method for preparing Ag / TiO2 nano-particles with core-shell structure at normal temperature and application
CN112058260A